Real World Clinical Utility of Neurophysiological Measurement Utilizing Closed-Loop Spinal Cord Stimulation in a Chronic Pain Population: The ECAP Study Protocol - Leitner A; Hanson E; Soliday N; Staats P; Levy R; Pope J; Kallewaard JW; Doleys D; Li S; Weisbein J; Amirdelfan K; Poree L (Journal of Pain Research, 2023)
Angela Leitner,1 Erin Hanson,1 Nicole Soliday,1 Peter Staats,2 Robert Levy,3 Jason Pope,4 Jan W Kallewaard,5,6 Daniel Doleys,7 Sean Li,2 Jacqueline Weisbein,8 Kasra Amirdelfan,9 Lawrence Poree10 1Saluda Medical Pty Ltd, Artarmon, New South Wales, Australia; 2National Spine and Pain Centers, Shrewsbury, NJ, USA; 3Departments of Neurosurgery and Clinical Research, Anesthesia Pain Care Consultants, Tamarac, FL, USA; 4Evolve Restorative Center, Santa Rosa, CA, USA; 5Department of Anaesthesiology and Pain Management, Rijnstate Hospital, Arnhem, the Netherlands; 6Department of Anesthesiology and Pain Medicine, Amsterdam University Medical Centre, Amsterdam, the Netherlands; 7Pain and Rehabilitation Institute, Birmingham, AL, USA; 8Napa Valley Orthopaedic Medical Group, Napa, CA, USA; 9Boomerang Healthcare, Walnut Creek, CA, USA; 10Department of Anesthesia and Perioperative Care, University of California at San Francisco, San Francisco, CA, USACorrespondence: Angela Leitner, Saluda Medical, Ground Floor, 407 Pacific Hwy, Artarmon, NSW, 2064, Australia, Email angela.leitner@saludamedical.comBackground: Spinal cord stimulation (SCS) is an established chronic pain treatment, but the effectiveness of traditional, open-loop paradigms has been plagued by variable sustainability in a real-world setting. A new approach, utilizing evoked compound action potential (ECAP) controlled closed-loop (CL) SCS, continuously monitors spinal cord activation and automatically adjusts the stimulation amplitude of every pulse, maintaining stimulation at the prescribed ECAP level through this continual feedback mechanism. Recent studies demonstrated the long-term safety and efficacy of ECAP-controlled CL-SCS. Here, we report the design of a prospective, multicenter, single-arm feasibility study to characterize clinical outcomes in a real-world chronic pain population utilizing ECAP-controlled CL-SCS. Objective neurophysiological measurements such as device performance and patient therapy compliance, will be analyzed against baseline biopsychosocial assessments, to explore the clinical utility of these objective physiologic biomarkers in patient phenotyping.Methods: This study will enroll up to 300 subjects with chronic, intractable trunk and/or limb pain in up to 25 United States investigation sites. Subjects meeting eligibility criteria will undergo a trial procedure and a permanent implant following a successful trial. Neurophysiological measurements (measured in-clinic and continuously during home use) and clinical outcomes including pain, quality-of-life, psychological, emotional, and functional assessments will be collected at baseline, trial end, and up to 24-months post-implantation.Discussion: Associations between objective neurophysiological data, clinical evaluation and patient-reported outcomes may have important clinical and scientific implications. They may provide novel insights about the chronic pain pathophysiology, its modulation during CL-SCS, and identification of pain phenotypes and/or mechanisms associated with treatment response during SCS trials and long-term therapy. Data from the ECAP study could lead to improvements in diagnosis, assessment, patient identification and management of chronic pain. It could also provide the foundation for development of a new SCS treatment approach customized by the patient’s pain phenotype, unique neurophysiology, and disease severity.Keywords: chronic pain, closed-loop, evoked compound action potentials, spinal cord stimulation